PERAN PENYULUH PERTANIAN TERHADAP PENINGKATAN PRODUKSI USAHATANI DI KABUPATEN PONTIANAK - SUNDARI, SUNDARI; A.YUSRA, ABDUL HAMID; NURLIZA, NURLIZA (Jurnal Social Economic of Agriculture, 2015)
The purpose of this thesis is " To know the relationship between the role of extension with increased production of rice farming in Pontianak regency ". The method used in this study using the survey locations Pinyuh River District and the District Anjongan.Variables examined in the study are as follows : 1) The role of the Advisory Extension, 2) Extension Role as Technician, 3) Role as Liaison Extension, 4) Extension Role as Organizer, 5) Role as Agent Extension Renewal. The analysis used in this study include : 1) Test Validity, 2) Test Reliability and 3) Kendall Tau test. The results of this study 1) Role of Agricultural Extension sufficiently contribute to Increased Production of Rice Farming in Pontianak regency. 2) The role of the Council for Agriculture, Technician, Liaison and Organizer in District Sui. Pinyuh to Increased Rice Production Anjongan better than the District. While the role of the Agricultural Extension Agents in District Sui Reformer. Anjongan Pinyuh and the District have a similar role to Increased Farm Production Padi. 3) Role of Agricultural Extension Difference in District and Sub-District Sui.Pinyuh Anjongan to Increased Rice Production allegedly difference farmer education and extension capabilities in conducting counseling. Keywords : Role Extension , Production of Rice Farming